Does the timing of treatment with intra-aortic balloon counterpulsation in cardiogenic shock due to ST-elevation myocardial infarction affect survival?. (June 2014) - Bergh, Niklas; Angerås, Oskar; Albertsson, Per; Dworeck, Christian; Matejka, Göran; Haraldsson, Inger; Ioanes, Dan; Libungan, Berglind; Odenstedt, Jacob; Petursson, Petur; Ridderstråle, Wilhelm; Råmunddal, Truls; et al.
Abstract Background: Intra-aortic balloon pump (IABP) counterpulsation and primary percutaneous coronary intervention (PCI) are standard treatment modalities in cardiogenic shock (CS) complicating acute myocardial infarction. The aim of this study was to investigate the impact of the timing of IABP treatment start in relation to PCI procedure. Methods: Data were obtained from the SCAAR registry (Swedish Coronary Angiography and Angioplasty Registry) about 139 consecutive patients with CS due to ST-elevation myocardial infarction (STEMI) who received IABP treatment. The patients were hospitalized at Sahlgrenska University Hospital, Gothenburg, during 2004–2008. The cohort was divided into the two groups: group (A) in whom IABP treatment started before start of PCI (n = 72) and group (B) in whom IABP treatment started after PCI treatment (n = 67). The primary endpoint was 30-day mortality. Propensity score (PS) adjusted Cox proportional hazards regression was used to analyze predictors of 30-day mortality. Results: Mean age was 66.5 ± 12 and 28% were women. All patients have received IABP treatment 30 min before or 30 min after primary PCI. 63% had diabetes and 28% had hypertension. 16% were active tobacco smokers. The mortality rate at 30 days was 38%. IABP treatment commenced before or after PCI was not an independent predictor of mortality (P = 0.72). Conclusion: In this non-randomized trial the treatment with insertion of IABP before primary PCI in patients with CS due to STEMI is not associated with a more favorable outcome as compared with IABP started after primary PCI.